A derradeira ilumiara de Ariano Suassuna: uma análise da voz narrativa no Romance de Dom Pantero no Palco dos Pecadores - Carneiro, Bárbara Maria Nunes Pereira (2021)
In the present dissertation, aspects of the narrative voice of Ariano Suassuna's ultimate ilumiara, Romance de Dom Pantero no Palco dos Pecadores are analyzed. Initially, we probe the process of consolidation of Suassuna's authorial voice throughout his trajectory on the literary scene. Then, we investigate the presence of autobiographical notes, the dialogue with some precursor voices, and the relationship of this prose with the Suassunian poetic voice. We rely on the theoretical support of authors such as Lejeune (2008), Arfuch (2010), Hervot (2013), Velasco (2015) and statements by Suassuna himself. We also looked into the texts of Tavares (2007), Dimitrov (2011) and Newton Junior (2017), experts on the Suassunian work. We visited discussions about the theory of the narrator, trying to identify what kind of narrator is not the narrator of the Suassunian ilumiara; Benjamim (1994), Auerbach (1976), and Dal Farra (1978) accompanied us in this incursion. When dealing with the dialogue with Tradition and the constitution of a selection of precursors of the narrative voice, we counted on the theoretical support of authors such as Borges (1999) and in the chapter referring to the role of the poetic voice in the Romance de Dom Pantero, studies such as the ones by Simões (2016), Paz (1993) and Lucáks (2000) served as support for the development of our discourse of understanding. The theoretical reading was collated with the fictional text, from which the citation was imperatively imposed in this exposition. We have inferred, therefore, that autobiographical aspects play a determining role in the formation of meanings in the text, but do not hinder it in the sphere of autofiction, which is extrapolated by the work of artistic creation of the narrated matter whose source and index is illustrated in the Suassuna poetry collected in this work under the pseudonym Albano Cervonegro and that serves in Dom Pantero as a kind of map for the encounter with this narrative voice that becomes as new as it is ancient.